Temporary Camps, Enduring Segregation The Contentious Politics of Roma and Migrant Housing - Maestri, Gaja (Palgrave Studies in European Political Sociology, 2019)
"In this theoretically challenging and empirically well researched volume, the protracted temporariness of camps is explained by looking at the contentious politics between state and non-state actors." -- Donatella della Porta, Scuola Normale Superiore, Italy. This book interrogates the persistence of Roma and migrant segregation in camps in order to understand how the creation of temporary enclosures can lead to enduring marginalisation. Persistent temporariness has been widely acknowledged as a common aspect of these camps, yet it remains largely under-theorised. Gaja Maestri unpacks the notion of camp persistence to delineate its different regimes and to investigate contributing factors. In order to do so, she develops a comparison between Italy and France and offers a new theorisation of the camp as a site of contentious politics, where the interaction between governmental and non-governmental actors produces different temporal arrangementsand forms of segregation. Temporary Camps, Enduring Segregation will be of interest to scholars of political sociology, European comparative politics, and urban geography, specifically to those in the field of camp studies, racial segregation, Romani studies, and urban social movements. .